2020
DOI: 10.1371/journal.pone.0240326
|View full text |Cite
|
Sign up to set email alerts
|

Addressing immediate public coronavirus (COVID-19) concerns through social media: Utilizing Reddit’s AMA as a framework for Public Engagement with Science

Abstract: COVID-19 has highlighted an opportunity for medical professionals to engage in online Public Engagement with Science (PES). Currently a popular platform for PES is Reddit. Reddit provides an Ask Me Anything (AMA) format for subject matter experts to answer questions asked by the public. On March 11, 2020, from 2:00 to 4:00pm EST, two Emergency Department physicians from Massachusetts General Hospital hosted an AMA session on coronavirus. We retroactively conducted an analysis of the questions and answers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…Although the increase in testing capacity nationally has improved (as of 6 November, Arkansas medical centers reported receiving a majority of test results within three days), the time between testing and return of results to patients is still at risk of significant delays as the number of COVID-19 cases rise [ 36 ]. This finding also highlights the importance of providing clear communication to patients about the need to quarantine as they wait for test results [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the increase in testing capacity nationally has improved (as of 6 November, Arkansas medical centers reported receiving a majority of test results within three days), the time between testing and return of results to patients is still at risk of significant delays as the number of COVID-19 cases rise [ 36 ]. This finding also highlights the importance of providing clear communication to patients about the need to quarantine as they wait for test results [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It raised concerns and anxiety among many users [ 13 , 74 ] and may have confused and distracted people, while causing harm to their mental health [ 75 ]. Moreover, the spreading of misleading information is the most infectious disease resulting to more health problems including anxiety, depression and loneliness [ 12 ]. Besides, several individuals expressed negative feelings (such as anxiety, stress, fear, and nervousness) via social media, which may have increased similar feelings in others [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination of misleading and false information via social media has many negative psychological and social consequences for community members [ 10 , 11 ]. In fact, Dr. Tedros Ghebreyesus, Director-General of the World Health Organization (WHO), said, “the wrong information about COVID-19 may be the most infectious disease,” and noted that misinformation about the COVID-19 pandemic has spread just as rapidly as the virus itself [ 12 ]. The stress and shock greatly affected the social and psychological well-being of the public [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…73 A content analysis of 522 Reddit comments showed that the topic of symptoms accounted for 27% (141) of all comments, followed by the topic of prevention (25% [131]). 74 Likewise, another content analysis of 155 353 unique English tweets showed that the most mentioned topic was "peril of COVID-19". 76 Additionally, a study that examined 126 049 English tweets by use of sentiment analysis and latent Dirichlet analysis for topic modelling showed that the most common emotion that was mentioned was fear, and the most common topic that was mentioned was the economic and political effects.…”
Section: Social Media For Surveillance and Monitoringmentioning
confidence: 99%